Feasibility study of cryoballoon ablation for atrial fibrillation with KODEX-EPD: a single center experience - Subinuer Wubulikasimu; Liang Wang; Suxia Yang; Wanyue Sang; Yafan Han; Lu Wang; Feifei Wang; Xianhui Zhou; Jianghua Zhang; Qiang Xing; Zukela Tuerhong; Jiasuoer Xiaokereti; et al. (Scientific Reports, 2023)
Abstract To evaluate the feasibility of cryoballoon (CB) ablation of atrial fibrillation (AF) under the guidance of a new three-dimensional (3D) mapping system KODEX-EPD. 40 patients scheduled for CB ablation of AF in the first affiliated Hospital of Xinjiang Medical University from August 2021 to July 2022 were randomly divided into two groups: KODEX-EPD 3D mapping system guidance group (KODEX group, n = 20) and conventional two-dimensional perspective group (standard group, n = 20). The ablation time, operation time, fluoroscopy time, fluoroscopy dose, contrast agent dosage and follow-up data were compared between the two groups. Besides, the feasibility and accuracy of the dielectric sensing system in evaluating pulmonary vein (PV) occlusion in patients with AF during CB ablation were verified. All pulmonary veins were being isolated. The ablation time (36.40 ± 6.72 min vs 35.15 ± 6.29 min, P > 0.05) and the operation time (64.20 ± 11.82 min vs 66.00 ± 13.18 min, P > 0.05) were not statistically different in the two groups. The standard group has longer fluoroscopy time, dose and contrast medium dosage. There were significant differences in fluoroscopy time (532.30 ± 72.83 s vs 676.25 ± 269.33 s, P < 0.05), fluoroscopy dose (110.00 ± 28.64 mGy vs 144.68 ± 66.66 mGy, P < 0.05), and contrast medium dosage (71.90 ± 5.97 ml vs 76.05 ± 5.93 ml, P < 0.05) between the two groups. The learning curves of the first 5 patients and the last 15 patients in the KODEX group were compared. There was no statistical difference in the ablation time (36.80 ± 8.56 min vs 36.27 ± 6.34 min, P > 0.05) or the operation time (69.00 ± 5.00 min vs 62.60 ± 13.10 min, P > 0.05); however, compared to the first 5 patients, fluoroscopy time (587.40 ± 38.34 s vs 513.93 ± 73.02 s, P < 0.05), fluoroscopy dose (147.85 ± 35.19 mGy vs 97.39 ± 8.80 mGy, P < 0.05) and contrast medium dosage (79.60 ± 1.14 ml vs 69.33 ± 4.45 ml, P < 0.05) were significantly decreased. Using pulmonary venography as the gold standard, the sensitivity, specificity of the completely occlusion in KODEX group was 93.6% (95% CI 85–97.6%) and 69.6% (95% CI 54–81.8%); and the sensitivity, specificity of the small leak in KODEX group was 93.1% (95% CI 82.4–97.8%) and 82.0% (95% CI 65.9–91.9%). During an average follow-up of (9.90 ± 1.06) months, there was no statistical difference in arrhythmia recurrence and antiarrhythmic drugs taking after CB ablation between the two groups (P > 0.05). Using the KODEX-EPD system, the CB ablation procedure can correctly evaluate the PV occlusion, and significantly reduce fluoroscopy exposure and contrast medium without significantly increasing the operation time.